The Inspection of Education: the evaluation function of the Inspection - Rul Gargallo, Jesús (Avances en Supervisión Educativa, 2006)
Starting from the statement that the Education Inspectorate is the body for the control of formal education par excellence, the nature of the Inspectorate and the duties of control assigned to it are analysed upon different outlooks. In this framework, the evaluating task and its repercussions in organization and duties are analysed in detail. The view provided by the analysis allows to take new challenges and identify values for the consolidation of the Education Inspectorate as state professional body with responsabilities in education over supervision, evaluation and consulting.